(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to demonstrate the effect of disclosing future aspirations (DFA) on the future financial performance of industrial companies listed on Amman Stock Exchange for the period 2013-2017. To achieve the purpose of this study, the researcher collected the relevant data to complete the study through the published annual financial reports for the industrial companies that represent the study sample with a percentage of 79.03% out of the total 62 industrial companies listed on Amman Stock Exchange. The multiple linear regression was used to show the effect of disclosing future aspirations on the future financial performance. One of the most important findings of the study is that there was no statistically significant effect at the level of significant (α ≤ 0.05) of disclosing future aspirations on the future financial performance with its indicators (return on assets, return on shareholders equity, earning per share). The study has come up with a set of recommendations, the most important of which is thatit is necessary to review the current traditional model for preparing annual financial reports, so that it largely influences on the future activities of the company and the assumptions on which it is based.